2021
DOI: 10.1177/09637214211040771
|View full text |Cite
|
Sign up to set email alerts
|

The Missing Side of Acculturation: How Majority-Group Members Relate to Immigrant and Minority-Group Cultures

Abstract: In many countries, individuals who have represented the majority group historically are decreasing in relative size and/or perceiving that they have diminished status and power compared with those self-identifying as immigrants or members of ethnic minority groups. These developments raise several salient and timely issues, including (a) how majority-group members’ cultural orientations change as a consequence of increasing intercultural contact due to shifting demographics; (b) what individual, group, cultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 32 publications
(37 reference statements)
0
35
0
Order By: Relevance
“…However, acculturation attitudes are commonly assessed by combining attitudes toward only minority group members’ (a) maintenance of their heritage culture and (b) dominant culture adoption (Bourhis et al, 1997 ). Following theoretical considerations on the reciprocity and mutuality of acculturation (Chirkov, 2009 ), empirical research has started assessing not only minority but also majority acculturation (Kunst et al, 2021 ). However, assessing attitudes toward both minority and majority acculturation is still a research gap.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, acculturation attitudes are commonly assessed by combining attitudes toward only minority group members’ (a) maintenance of their heritage culture and (b) dominant culture adoption (Bourhis et al, 1997 ). Following theoretical considerations on the reciprocity and mutuality of acculturation (Chirkov, 2009 ), empirical research has started assessing not only minority but also majority acculturation (Kunst et al, 2021 ). However, assessing attitudes toward both minority and majority acculturation is still a research gap.…”
Section: Introductionmentioning
confidence: 99%
“…Diversity approaches at school were found to affect ethnic minority and majority adolescents (Baysu et al, 2021 ), illustrating schools’ agency as well as how immigrant-background and non-immigrant-background students are affected by it. Majority-group members and institutions thus become recipients and minority-group members become agents of social change (Kunst et al, 2021 ). Therefore, instead of focusing only on minority students as acculturating agents, majority students and schools are also considered in this study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 25 ] proposed a list of external factors potentially affecting acculturation: the existence of ethnic enclaves and the dominant culture’s values, behaviour, and attitudes, which may change according to the native’s perception of the motive for migration [ 45 ]. In fact, several of the present results point to the importance of assessing the behaviour of the receiving society towards foreign cultures; which exerts great influence on the cultural orientation of foreigners [ 46 ]. Hence, it is suggested that Carlson and Güler’s [ 34 ] conception of cultural preference could be used to place the local society within a continuum, from allowing the substitution of the majority’s culture, to demanding foreigners for cultural assimilation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 48 ] to define the status of an influential demonstrator [ 49 ]. Fourth, the acculturation domain (public or private) and cultural distance (the degree of dissimilarity between the Italian/Portuguese and the foreign cultures) could also have been accounted for [ 46 ], despite no significant differences being observed between the Italian and Portuguese samples.…”
Section: Discussionmentioning
confidence: 99%